Complete Genome Sequences of the Plant Pathogens Dickeya solani RNS 08.23.3.1.A and Dickeya dianthicola RNS04.9 - Khayi, Slimane; Blin, Pauline; Chong, Teik Min; Robic, Kevin; Chan, Kok Gan; Faure, Denis (American Society for Microbiology, 2018)
Dickeya spp. are bacterial pathogens causing soft-rot and blackleg diseases on a wide range of ornamental plants and crops. In this paper, we announce the PacBio complete genome sequences of the plant pathogens Dickeya solani RNS 08.23.3.1.A (PRI3337) and Dickeya dianthicola RNS04.9.